Techniki ustanawiania ekwiwalencji w wybranych tekstach stylu urzędowego z XVII i XVIII wieku - Osowski, Błażej (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
Equivalence may be interpreted as the relationship between units of the same language or two different languages. The article analyses the equivalence between units of the same linguistic system, with the assumption that equivalence is the relationship between words/phrases with a common referent. This is a semantic relationship strongly dependent on context; one which is fully realised only on the level of parole, a specific use. The analysed material comprises inventories, surveys and testaments from the seventeenth and (mostly) eighteenth centuries. The aim of the article is to present the methods for determining equivalence between the units present in the text. Seven of such methods are highlighted.